Relationship Between Type Of Delivery And Completeness Of Postpartum Visit In The Working Area Of Puskesmas Kampung Delima, Rejang Lebong Regency - Hilmiffah, Destyanie; Sari, Liya Lugita; Jumita, Jumita (Student Scientific Journal, 2025)
Mothers who give birth by cesarean, vacuum and forceps tend to make postpartum visits compared to mothers who give birth normally. to find out the relationship between the type of delivery with the completeness of postpartum visits in the Working Area of Puskesmas Kampung Delima Rejang Lebong Regency The population in this study were postpartum women > 40 days in the Working Area of Puskesmas Kampung Delima in the period May to June 2024 totalling 42 people. The research sample was postpartum women >40 days in the Kampung Delima Health Centre Working Area. Sampling in this study was conducted using total sampling technique. Of the 42 respondents, almost all respondents (85.7%) had normal labour. The analysis using the Chi-Square test obtained a p-value = 0.023 < α = 0.05, meaning that there is a relationship between the type of delivery and the completeness of postpartum visits in the Working Area of Puskesmas Kampung Delima, Rejang Lebong Regency It is hoped that in order to increase postpartum visits, Puskesmas can collaborate with husbands and Posyandu cadres so that postpartum women can make postpartum visits so that midwives can carry out early detection of complications that occur during the postpartum period.